2021
DOI: 10.1136/bmjopen-2021-049160
|View full text |Cite
|
Sign up to set email alerts
|

Association between ambient temperature and cognitive function in a community-dwelling elderly population: a repeated measurement study

Abstract: ObjectivesEvidence on the associations between short-term and long-term air temperature exposure and cognitive function in older adults, particularly those in Asia, is limited. We explored the relationships of short-term and long-term air temperature exposure with cognitive function in Taiwanese older adults through a repeated measures survey.Design and settingWe used data the ongoing Taiwan Longitudinal Study on Aging, a multiple-wave nationwide survey.ParticipantsWe identified 1956, 1700, 1248 and 876 older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…It assesses their orientation regarding place, personal information, and time. The SPMSQ has been described as a valid and reliable measure for assessing cognitive status in older adults [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…It assesses their orientation regarding place, personal information, and time. The SPMSQ has been described as a valid and reliable measure for assessing cognitive status in older adults [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another study based on a systematic review and meta-analysis in 2016 produced similar results and additionally found that increased temperature was associated with increased risk of diabetes mellitus, stroke, and infectious disease 3 . Beyond these effects, increased temperatures are also expected to affect cognitive function 4,5 and sleep quality 6 among older adults.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies primarily examine short-term temperature exposures, there is evidence that long-term exposure to higher temperatures may also worsen cognitive decline. A longitudinal study of older adults in Taiwan found that each degree Celsius increase in both long-and short-term exposure was signi cantly associated with higher odds of moderate to severe cognitive impairment 5 . In contrasting results, a cross-sectional study of American older adults found that high-temperature exposure was not signi cantly related to changes in cognitive function 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Older adults with the risk of low MMSE scores demonstrated a significant U-shaped association with residential ambient temperature and culminated at extreme high or low temperatures 15 . The risk of mild cognitive impairment among community-dwelling older adults in Taiwan aggrandized with rising ambient temperature 22 . Lower temperatures were associated with an increased risk of impaired cognitive ability 23 and lower cognitive scores in older adults 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies had investigated and revealed the heterogeneity of the impacts of environmental temperature exposure on cognitive function in terms of different subgroups of older adults, in which the quantitative relationship between older adults with different sociodemographic characteristics, geographical distribution 15 , 31 , individual physiological diatheses 16 , 22 , 23 , and lifestyles or habits 15 , 23 and temperature variations were analyzed separately. Some of these heterogeneity results were significant, which verified the necessity of exploring the differences in the cognitive function of the Chinese older adults influenced by temperature.…”
Section: Introductionmentioning
confidence: 99%